Navigating the path to equitable rheumatologic care for underserved children with quality improvement - Vora, Sheetal S.; Mabus, Sarah C.; Buitrago-Mogollon, Talia L. (Frontiers in Pediatrics, 2024)
Objective. The aim of this Quality Improvement (QI) project was to identify children with rheumatologic conditions to prevent delayed or missed diagnosis in underserved pediatric populations. Our focus was on prompt and accurate identification and subsequent treatment of rheumatologic symptoms for pediatric patients referred from Atrium Health safety-net primary care clinics which deliver care to families without private insurance, including those lacking insurance entirely.Methods. We collaborated with providers at one safety-net clinic to increase identification and subspecialty referral for pediatric patients with potential rheumatologic disease. We used the Model for Improvement framework with rapid Plan-Do-Study-Act cycles and evaluated improvement with run and statistical process control charts.Results. We achieved improvement, increasing from zero referrals in the previous five years for the targeted population to 15 patient referrals within one year of project initiation. Despite this surge increase in referrals, the rheumatology clinic was still able to see all priority patients within 20 business days from referral.Awareness of concerning rheumatology rheumatologic symptoms in safety-net primary care clinics combined with use of both visual and decision aids allows care teams to efficiently recognize and accurately refer patients needing specialty care.